The limited link between accommodation space, sediment thickness, and inner platform facies distribution (Holocene–Pleistocene, Bahamas). (19th September 2018) - Weij, Rieneke; Reijmer, John J. G.; Eberli, Gregor P.; Swart, Peter K.
Abstract: Cyclic facies variations in shallow‐water carbonate platforms often show repetitive facies patterns that are frequently interpreted to reflect the sedimentary response to variations in sea‐level related to changes in climate linked to orbital variations, the Milankovitch frequencies. Whether these shallow‐marine carbonates represent a complete infill of accommodation space, or are subtidal cycles, has been discussed in numerous papers. The extent to which the thickness of a single depositional cycle is a direct measure of the amplitude of relative sea‐level change is not fully understood. New shallow seismic data from Great Bahama Bank reveal that accommodation space created during the Holocene sea‐level rise is not filled in a predictable way. Three seismic horizons were identified: the seabed, the Pleistocene top, and a horizon within the Pleistocene. Depth surface and thickness maps of the Holocene and Pleistocene layers were combined with 326 in situ water‐depth measurements to assess the upper limit of the present accommodation space. The analysis showed that accommodation space and Holocene sediment thickness, and water depth are not correlated. In addition, the actual water depth and inner platform facies distribution showed no straightforward link. The energy distribution across the shallow‐water platform appears to control the facies type rather than water depth. Mud‐dominated sediments prevail in shallow low‐energy areas protected by a topographic barrier, whereas mud‐free coarse‐grained sediments mainly occur in deeper areas with hydrodynamic energy induced by strong tidal currents, ocean water influx, and winds. Hence, the uneven energy distribution not only results in unpredictable differences in the carbonate‐cycle thickness on the platform but also to a water depth independent facies distribution pattern within the inner platform. Therefore, care should be taken when deducing sea‐level signals from inner platform facies distribution and sediment thickness patterns on ancient platforms. Abstract : New seismic data from the shallow subsurface of Great Bahama Bank show that sedimentation cycle thicknesses of the studied Holocene and Pleistocene shallow‐marine carbonates are not in equilibrium with the amplitude of orbitally driven sea‐level change and associated infill of accommodation space. The energy distribution across the shallow‐water platform appears to be uneven and to control the facies type rather than water depth. This results in unpredictable differences in carbonate‐cycle thickness on the platform and a water‐depth independent facies distribution pattern within the inner platform.